Pengaruh Penggunaan Mulsa Pada Berbagai Jarak Tanam Terhadap Pertumbuhan Dan Hasil Bawang Merah Varietas Lembah Palu - Adnan Adnan (Universitas Tadulako, 2019)
This study aims to determine the effect of mulch using different plant spacing on growth and yield of shallot Palu valley varieties. This study was conducted in December 2017 to February 2018. The was field experiments using a split plot design with the main plot is a type of mulch consists of : without mulch, mulch rice husk, and mulch sawdust. The subplot is a spacing comprising: a spacing of 10 cm x 20 cm, 15 cm x 20 cm and 20 cm x 20 cm. There are nine combination treatment and combination treatment was repeated three times so that overall there are 27 experimental units. The results showed that: (1) There is no interaction between the use of mulch and different spacing on the growth and yield of shallot. (2) Mulch sawdust generating plant height, longest leaf length on destructive plants and weight of the fresh tubers per hectare eskip. While rice husk mulch produce fresh weight eskip tuber per clumps, tuber water content, diameter and length of the root tuber higher. Lowest growth and yield of shallot was found in without mulch treatment. (3) plant spacing treatment of 10 cm x 20 cm produce the number of leaves, number of tubers per clumps were higher respectively by 7.76 per clump. While the spacing of 15 cm x 20 cm of fresh weight yield per hectare of tubers with a higher leaf 7,12 ton / ha. At a spacing of 20 cm x 20 cm of fresh weight tuber yield per hectare eskip of 4.36 tons / ha.